Ingroup Love and Outgroup Hate, or just ‘Concern’? The Role of National Identification and Prejudice in the relation between Intragroup Communality and Reservations about Newcomers - Waldzus, S.; Sekerdej, M. (22nd Jena Workshop on Intergroup Processes: National Identity: Its nature, causes, and consequences, 2022)
The current war in Ukraine has put in the spotlight the implications of nationalism for intergroup relations for the rejection or acceptance of immigrants and refugees, especially in countries bordering Ukraine. The classical ethnocentrism hypothesis would predict an inverse relation between strong communal bonds among nationals and hostility towards outsiders, but more contemporary accounts to intergroup relations draw a sharper distinction between ingroup communality (ingroup love) and attitudes towards outgroups (outgroup hate), emphasizing independence between the two. Research directly testing these ideas is scarce. We will present three studies (total N = 311) examining the relationship between communal intragroup relations between Polish nationals and attitudes toward immigrants. Data were collected years before the current war in Ukraine when refugees were more coming from Middle-eastern and African countries, but the economic immigration from Ukraine was already strong. As hypothesised, intragroup communality was not directly, but indirectly linked to outgroup negativity, mediated by ingroup identification. More precisely, there was a positive statistical mediation chain leading from ingroup communality among host society nationals via ingroup attachment and glorification to intergroup threat and social distance (Studies 1-3), which also had consequences for relational exclusivity against immigrants, that is, strong relational demands that newcomers must fulfil before being accepted (Studies 2-3). The mediation by glorification, was strengthened by experimental induction of the salience of superiority (Study 3). Moreover, findings regarding a parallel mediation chain leading from intragroup communality via egalitarian beliefs to outgroup positivity were not consistent. Overall, the findings support the suspicion that there is a robust dark side of nationalism, due to the indirect association between ingroup communality and outgroup negativity via national identification. In contrast, the extension of ingroup love to outgroup members, for instance via equality beliefs, seems to depend on particular conditions.